2006
DOI: 10.1021/ma060047q
|View full text |Cite
|
Sign up to set email alerts
|

Minimization of Internal Molecular Free Volume:  A Mechanism for the Simultaneous Enhancement of Polymer Stiffness, Strength, and Ductility

Abstract: We have synthesized and analyzed the mechanical/structural characteristics of a polyester containing 21 wt % of a triptycene monomer and compared it to a reference polyester homologue wherein benzene replaces the triptycene residue. Solvent-cast films and tension heat-treated (THT) films were investigated by tensile deformation and wide-angle X-ray scattering. The addition of triptycene units increases the T g and, contrary to what is typically observed, also increases the ductility of film samples. In compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
172
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(182 citation statements)
references
References 28 publications
6
172
2
Order By: Relevance
“…Triptycene, as shown in Figure 1a, has three phenyl rings bound by a single hinge, which provides a high energy barrier to molecular twisting or deformation which keeps the angle between aromatic rings at 120 o . The rigid 3-dimensional, fully aromatic structure leads to poor polymer chain packing, which, in turn, results in high internal free volume (IFV) [26,27]. An extended iptycene building block, shown in Figure 1b, demonstrates even larger IFV than triptycene due to the addition of a benzene ring to the transverse aromatic arm in the 9,10-position of the triptycene unit.…”
Section: Introductionmentioning
confidence: 99%
“…Triptycene, as shown in Figure 1a, has three phenyl rings bound by a single hinge, which provides a high energy barrier to molecular twisting or deformation which keeps the angle between aromatic rings at 120 o . The rigid 3-dimensional, fully aromatic structure leads to poor polymer chain packing, which, in turn, results in high internal free volume (IFV) [26,27]. An extended iptycene building block, shown in Figure 1b, demonstrates even larger IFV than triptycene due to the addition of a benzene ring to the transverse aromatic arm in the 9,10-position of the triptycene unit.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Recently, some studies suggest that local cavities can be formed due to the inability for triptycene-based polymeric structures to pack efficiently. [17] Because of these features, triptycene-based polymers, or molecules have been developed for gas adsorption as well as membrane-based gas separation, providing large BET surface area within 600-1 800 m 2 Á g À1 as well as high microporosity.…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with previous research, which has found that triptycene can increase the thermal stability of polymers. [18][19][20] Interestingly, the block copolymers do not show increasing thermal stability with higher triptycene content. Presumably, this is because the molecular weight of PT1 1 -b-PO 1 is lower than the weights of the PT1 1 -b-PO 3 copolymers.…”
Section: Thermal Propertiesmentioning
confidence: 95%
“…Enhanced thermal stability is often also observed with triptycene incorporation, along with improvements in polymer mechanical properties including increased stiffness, toughness, ductility, and ultimate tensile strength. [19][20][21] In this study, we have systematically introduced triptycene into the backbone of ADMET-synthesized polyethers to investigate the thermal and mechanical effects of triptycene incorporation. Two different triptycene olefin monomers were synthesized to study the effect of incorporation into the polymer backbone in different geometries (Fig.…”
mentioning
confidence: 99%